ChemInform Abstract: Amino Acidic Scaffolds Bearing Unnatural Side Chains: An Old Idea Generates New and Versatile Tools for the Life Sciences. Issue 3 (January 2015) - Stevenazzi, Andrea; Marchini, Mattia; Sandrone, Giovanni; Vergani, Barbara; Lattanzio, Maria
Abstract Review: 54 refs.